Postoperative diagnosis of pulmonary actinomycosis in a patient with bronchiectasis ‒ a rare case - Kertmen, Muhammet; Cullu, Kübra; Gözükücük, Gülsah Kolak; Dubus, Turkan; Büyükpınarbasili, Nur (Rzeszów University Press, 2025)
Introduction and aim. Pulmonary actinomycosis is a rare chronic infection caused by Actinomyces species, often mimicking tuberculosis, malignancy, or other chronic lung diseases both clinically and radiologically. These similarities frequently lead to diagnostic delays. We present a rare case of pulmonary actinomycosis in a patient with long-standing bronchiectasis who developed acute hemoptysis during anticoagulant therapy. Description of the case. A 59-year-old woman with a ten-year history of bronchiectasis and recent mechanical aortic valve replacement presented with persistent hemoptysis while on warfarin. Thoracic computed tomography revealed bronchiectatic changes and opacities in the right middle lobe. Bronchoscopy showed bloody, encrusted material, but no definitive diagnosis was made. Due to ongoing symptoms and radiological suspicion of malignancy, an urgent right middle lobectomy was performed. Histopathological analysis confirmed pulmonary actinomycosis, revealing filamentous organisms via PAS, Gram, and Grocott’s staining. Conclusion. This case highlights the importance of considering pulmonary actinomycosis in patients with bronchiectasis and unexplained hemoptysis, particularly when standard treatment fails. Surgical resection may be essential for both diagnosis and treatment. The case underscores how structural lung disease and anticoagulant use can reveal rare infections otherwise masked by chronic symptoms.
Written informed consent was obtained from the patient for the use of clinical data, medical images, and related information presented in this case report. The patient was assured that all personally identifiable information would be treated confidentially and that all data would be anonymized to protect privacy.
Keywords: actinomycosis; bronchiectasis; hemoptysis; lobectomy; pulmonary infection